An integrated approach to studying the structure of ternary CoCrMo alloy: scanning electron microscopy and atomistic simulation - D.A. Kravchenko; A.Yu. Kolosov; D.N. Sokolov; N.I. Nepsha; S.S. Bogdanov; N.Yu. Sdobnyakov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
A comparative study combining the experimental technique of scanning electron microscopy and atomistic simulation by (molecular dynamics) was carried out using of the ternary CoCrMo nanoalloy as an example. Employing the technology of selective laser melting based on the PR-KH28M6 powder, a sample was made for which a non-uniform surface composition with respect to the presence of cobalt and chromium was identified, i.e. areas were simultaneously enriched and depleted in these elements, which indicates the possibility of forming various intermetallic compounds based on them. In the process of atomistic simulation, three nanoparticles of the ternary CoCrMo nanoalloy with the number of 10000, 15000 and 30000 atoms were subjected to a sequential cycle of heating and cooling, including the identification of phase transitions corresponding to melting and crystallization, respectively. The corresponding temperatures of the beginning and end of the phase transition were determined. The regularities of structural and surface segregation in the ternary CoCrMo nanoalloy are described. It is noted that for nanoparticles containing 10000 atoms, only a shell of cobalt atoms is formed without forming a core, while for nanoparticles containing 15000 and 30,000 atoms, an onion-like structure is formed. Chromium atoms form either the core of the nanoparticle as at N=10000 or the peripheral region as at N=15000 and 30000. Molybdenum atoms behave indifferently, i.e. are distributed uniformly throughout the entire volume of the nanoparticles under study.